2022
DOI: 10.1038/s41598-022-12694-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comparison of monofocal, extended depth of focus and trifocal intraocular lens profiles

Abstract: To test the feasibility of using profilometers to extract information about IOL surfaces design. A standard monofocal IOL (Tecnis 1), a monofocal IOL that provided some depth of focus (Eyhance), an extended depth of focus IOL based on refractive optics (Mini Well) and a trifocal IOL based on diffractive optics were used in this study (Tecnis Synergy). The surface topography of the IOLs was measured by using a multimode optical profilometer. Posterior surface of Tecnis 1 IOL was spherical and the anterior surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The systematic reviews only included evidence for the Tecnis Eyhance IOL, which was for both laboratory and clinical studies, the enhanced monofocal IOL with the highest volume of evidence to date. Laboratory studies have reported optical quality of other enhanced monofocal IOLs such as RayOne EMV [20,[23][24][25], IsoPure [20,27], Zoe [20], Acunex Quantum [21], Lentis Quantum [22], and Vivinex Impress [27], but optical profiles have been only documented for Tecnis Eyhance [31,32]. However, laboratory or clinical studies have not been conducted for other announced enhanced monofocal IOLs such as Evolux and Extend HP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic reviews only included evidence for the Tecnis Eyhance IOL, which was for both laboratory and clinical studies, the enhanced monofocal IOL with the highest volume of evidence to date. Laboratory studies have reported optical quality of other enhanced monofocal IOLs such as RayOne EMV [20,[23][24][25], IsoPure [20,27], Zoe [20], Acunex Quantum [21], Lentis Quantum [22], and Vivinex Impress [27], but optical profiles have been only documented for Tecnis Eyhance [31,32]. However, laboratory or clinical studies have not been conducted for other announced enhanced monofocal IOLs such as Evolux and Extend HP.…”
Section: Discussionmentioning
confidence: 99%
“…The halo size was measured through the PSFcross section showing similar profiles of enhanced monofocals Tecnis Eyhance, Zoe and IsoPure in comparison to the standard monofocal [18][19][20]. With regard to surface profiles, two manuscripts presented the profile of the Tecnis Eyhance measured with the Talysurf CLI 1000 and Zeta Z300 profilometers and in comparison to standard monofocal and refractive EDOF lenses [31,32]. These studies demonstrated variations between the maximum and minimum elevations of the profiles below ± 1 µm for the standard monofocal, ± 2 µm for the enhanced monofocal, and ± 4 µm for the refractive EDoF.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…It is possible that patients at the six-month time interval experienced neuroadaptation, accounting for the reversal between the Synergy and PanOptix groups [15]. However, the spherical base curve of the diffractive surface of the Synergy IOL may help explain the relatively increased photic phenomena reported by Synergy patients since spherical surfaces have been associated with high-order aberrations and straylight [16,17]. The spherical base curve of the diffractive surface of the Synergy IOL may also explain enhanced mesopic performance and image contrast in these lenses when compared to PanOptix IOLs, as reported by Dick et al, and provide insight into the increased reported frequency of photic phenomena for Synergy patients [4,5,17].…”
Section: Discussionmentioning
confidence: 99%
“…The surface shape of the monofocal version of the Tecnis ® , the ZCB00, was studied by Miret et al 3 . Their work arrives at the conclusion of the anterior side being conic and the posterior side being spherical, both sides without higher order polynomials.…”
Section: Discussionmentioning
confidence: 99%
“…Similar work includes characterization of the diffractive properties of multifocal intraocular lenses by Loicq et al 2 , as well as measurement and decomposition of the monofocal lens base form by Miret et al 3 . Other papers derive optical properties from known mathematical lens descriptions, as can be found for the diffractive profile in the work of Vega et al 4 , and for monofocal intraocular lenses in the work of Barbero et al 5 .…”
Section: Introductionmentioning
confidence: 99%